A Survey on AI-Generated Content: From Technical Foundations to Ethical Challenges - Redgrave, Callum (Journal of Computer Science and Software Applications, 2025)
The emergence of AI-generated content (AIGC) technologies has transformed the landscape of digital media, communication, and knowledge generation. Driven by the rapid evolution of foundation models such as GPT, DALL·E, and Stable Diffusion, AIGC systems have demonstrated remarkable capabilities in generating human-like text, images, code, and multimedia. This paper provides a comprehensive review of the technical underpinnings, system-level architectures, and deployment workflows that support modern AIGC systems. It further explores critical ethical and societal concerns, including misinformation, authorship attribution, bias propagation, and the erosion of human agency. Through an examination of recent developments from 2023 to 2025, the paper evaluates the trajectory of AIGC integration across sectors such as education, entertainment, law, and journalism. Finally, we discuss emerging regulatory frameworks and outline key research directions to ensure responsible, transparent, and human-aligned advancement of generative AI.